3D graphene aerogels-supported Ag and Ag@Ag3PO4 heterostructure for the efficient adsorption-photocatalysis capture of different dye pollutants in water. (September 2018) - Chen, Fenghua; Li, Shuangshuang; Chen, Qingtao; Zheng, Xianjun; Liu, Porun; Fang, Shaoming
Graphical abstract: Ag3 PO4 are hetero-grown on partly Ag nanoparticles in macroporous 3D Ag/GA for efficient adsorption-photocatalysis capture of both cationic (RhB, MB, and NR) and anionic (MO) dyes. Highlights: 3D graphene aerogels-supported Ag and Ag@Ag3PO4 heterostructure are synthesized. The composite is effective in adsorption-photocatalysis cationic and anionic dyes. The apparent adsorption-photocatalysis removal sequence is NR > RhB > MB > MO. The contributions of adsorption and photocatalysis is different for different dyes. The composite exhibits the highest catalytic activities with excellent stability. Abstract: In this paper, we successfully synthesized 3D graphene aerogels-supported Ag and Ag@Ag3 PO4 heterostructure (3D Ag/Ag@Ag3 PO4 /GA) by the hetero-growth of Ag3 PO4 on partly Ag nanoparticles in macroporous 3D graphene aerogels (3D GA), aiming for the efficient adsorption-photocatalysis capture of both cationic (RhB, MB, and NR) and anionic (MO) dyes from aqueous solutions. For the removal of different dyes, the contributions of adsorption and photocatalysis is different and the apparent removal sequence is NR > RhB > MB > MO on the prepared 3D Ag/Ag@Ag3 PO4 /GA. Compared with bare Ag3 PO4 particles, Ag3 PO4 /GO, and Ag/Ag@Ag3 PO4 /GO, the prepared 3D Ag/Ag@Ag3 PO4 /GA exhibits the highest catalytic activities for the visible light degradation of RhB and MO. The possible mechanism for improved photocatalytic degradation of dyes by the 3D Ag/Ag@Ag3 PO4 /GA is proposed based on the active species trapping experiments. Moreover, the good stability and convenient recycling of the prepared 3D Ag/Ag@Ag3 PO4 /GA composite further make it have potential application prospect in eliminating organic contaminants.